The protease inhibitor JO146 demonstrates a critical role for CtHtrA for Chlamydia trachomatis reversion from penicillin persistence - Ong, Vanissa A. (Frontiers Media S.A., 2013)
The Chlamydia trachomatis serine protease HtrA (CtHtrA) has recently been demonstrated to be essential during the replicative phase of the chlamydial developmental cycle. A chemical inhibition strategy (serine protease inhibitor JO146) was used to demonstrate this essential role and it was found that the chlamydial inclusions diminish in size and are lost from the cell after CtHtrA inhibition without formation of viable elementary bodies. The inhibitor (JO146) was used in this study to investigate the role of CtHtrA for penicillin persistence and heat stress conditions for Chlamydia trachomatis. JO146 addition during penicillin persistence resulted in only minor reductions (~1 log) in the final viable infectious yield after persistent Chlamydia were reverted from persistence. However, JO146 treatment during the reversion and recovery from penicillin persistence was completely lethal for Chlamydia trachomatis. JO146 was completely lethal when added either during heat stress conditions, or during the recovery from heat stress conditions. These data together indicate that CtHtrA has essential roles during some stress environments (heat shock), recovery from stress environments (heat shock and penicillin persistence), as well as the previously characterized essential role during the replicative phase of the chlamydial developmental cycle. Thus, CtHtrA is an essential protease with both replicative phase and stress condition functions for Chlamydia trachomatis.